Systematic review of useful plants in the Colombian Orinoquia: A quantitative synthesis for biocultural management - Arévalo Marín, Edna; Montoya-Riveros, Anny (Ethnobotany Research and Applications, 2026)
Background: The Colombian Orinoquia is largely composed of a mosaic of savannas determined by drainage conditions, where useful plants underpin food, health, materials, and livelihoods. Yet information is scattered and uneven across places and cultures, limiting evidence-based biocultural management. A standardized baseline is needed to describe species–use patterns and remaining gaps. Methods: We followed PRISMA, harmonized published records, verified taxonomy, and compiled incidence matrices (studies × species; studies × categories). Diversity was estimated with coverage-based rarefaction/extrapolation (iNEXT, q=0). Redundancy was summarized with Hill numbers (q=1) and network structure with H2′, nestedness, and modularity. Relative Importance combined citation frequency and use versatility. Results: We included 44 studies. Species coverage was low (SC=0.574), with extrapolated richness ≈769 species (95% CI 674–863), while the 12 major categories appeared saturated. The dataset comprised 1,119 study–species–category records for 502 species in 92 families; Fabaceae and Arecaceae were most speciose. Records and species concentrated in Construction, Edible, Medicinal, Ornamental, and Handicrafts. Redundancy and evenness were high in most categories (e.g., Construction Reff=155.3; Ornamental 126.9). Network indices indicated low-to-moderate specialization and moderate compartmentalization (H2′=0.321; NODF=22.9; Q=0.470). High-RI taxa were dominated by palms, led by Mauritia flexuosa and Oenocarpus bataua. Conclusions: Major use categories are already represented, but incomplete species coverage and a right-skewed versatility distribution indicate many underreported taxa. High redundancy in leading categories and a moderately modular network suggest functional insurance in local practices. Priorities include standardized locality-specific surveys to raise coverage and targeted management of high-RI palms and context-relevant mid-rank species. Keywords: Llanos Orientales; Ethnobotany; Savannas.